Experimental Analysis on Shrinkage and Swelling in Ordinary Concrete - Kucharczyková, Barbara; Daněk, Petr; Kocáb, Dalibor; Misák, Petr (Hindawi Publishing Corporation, 2017)
The paper deals with the experimental determination of shrinkage development during concrete ageing. Three concrete mixtures were made. They differed in the amount of cement in the fresh mixture, 300, 350, and 400kg/m3. In order to determine the influence of plasticiser on the progress of volume changes, another three concrete mixtures were prepared with plasticiser in the amount of 0.25% by cement mass. Measurements were performed with the goal of observing the influence of cement and plasticiser content on the overall development of volume changes in the concrete. Changes in length and mass losses of the concrete during ageing were measured simultaneously. The continuous measurement of concrete mass losses caused by drying of the specimen’s surface proved useful during the interpretation of results obtained from the concrete shrinkage measurement. During the first 24 hours of ageing, all the concrete mixtures exhibited swelling. Its magnitude and progress were influenced by cement, water, and plasticiser content. However, a loss of mass caused by water evaporation from the surface of the specimens was also recorded in this stage. The measured progress of shrinkage corresponded well to the progress of mass loss.

The paper deals with the experimental determination of shrinkage development during concrete ageing. Three concrete mixtures were made. They differed in the amount of cement in the fresh mixture, 300, 350, and 400kg/m3. In order to determine the influence of plasticiser on the progress of volume changes, another three concrete mixtures were prepared with plasticiser in the amount of 0.25% by cement mass. Measurements were performed with the goal of observing the influence of cement and plasticiser content on the overall development of volume changes in the concrete. Changes in length and mass losses of the concrete during ageing were measured simultaneously. The continuous measurement of concrete mass losses caused by drying of the specimen’s surface proved useful during the interpretation of results obtained from the concrete shrinkage measurement. During the first 24 hours of ageing, all the concrete mixtures exhibited swelling. Its magnitude and progress were influenced by cement, water, and plasticiser content. However, a loss of mass caused by water evaporation from the surface of the specimens was also recorded in this stage. The measured progress of shrinkage corresponded well to the progress of mass loss.
Experimental Analysis on Shrinkage and Swelling in Ordinary Concrete
Keywords: shrinkage; swelling; concrete; plasticizer; mass loss; shrinkage drain; Hollan strain gauge; shrinkage; swelling; concrete; plasticizer; mass loss; shrinkage drain; Hollan strain gauge